Bronchopulmonary Dysplasia: An Overview - Gisondo CM; Donn SM (Dove Medical Press, 2020)
Carly M Gisondo, Steven M Donn Division of Neonatal-Perinatal Medicine, Department of Pediatrics, University of Michigan, Ann Arbor, MI, USACorrespondence: Steven M DonnUniversity of Michigan, 1540 East Hospital Drive, CW 8621, Ann Arbor, MI 48109-4254, USAEmail smdonnmd@med.umich.eduAbstract: Bronchopulmonary dysplasia (BPD) is the most common long-term respiratory morbidity of infants born prematurely. Historically thought to be a direct consequence of lung injury from mechanical ventilation and exposure to high concentrations of oxygen, recent evidence suggests that the BPD of today may be the result of altered lung development and altered alveolarization. In this paper, we will review historical and contemporary definitions of BPD as well as frequently used prevention and management strategies.Keywords: prematurity, respiratory distress syndrome, lung injury, bronchopulmonary dysplasia